2002
DOI: 10.1081/ceh-100108712
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Postural Changes of Baroreflex Gain in Normal and Hypertensive Pregnancies

Abstract: In order to understand the changes of baroreflex gain due to postural changes in normal pregnancies, we measured percentage changes (% changes) in blood pressure (SBP, DBP), heart rate (HR), stroke volume (SV), cardiac output (CO), total peripheral resistance (TPR) as well as cardiac autonomic nervous function (HF as an index of parasympathetic and LF/HF as an index of sympathetic function) and compared these parameters in normal pregnancies with those found in hypertensive pregnancies, such as chronic hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…The higher HR and lower HP mean are compatible with these changes. These results are in agreement with several studies that reported a lower parasympathetic contribution in pregnancy [11,15,35]. Expansion of blood volume may cause stretching of the sinoatrial node leading to a less effective vagal modulation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The higher HR and lower HP mean are compatible with these changes. These results are in agreement with several studies that reported a lower parasympathetic contribution in pregnancy [11,15,35]. Expansion of blood volume may cause stretching of the sinoatrial node leading to a less effective vagal modulation.…”
Section: Discussionsupporting
confidence: 93%
“…Some works advocated the activation of the renin-angiotensin system to explain the increase of sympathetic activity observed during pregnancy [38]. Some studies confirmed at the cardiac level the sympathetic activation observed at the level of muscle nerve sympathetic activity [37] with the observation the ratio of LF to HF power increased during pregnancy [14,15]. Our study LFnu did not show differences between groups, thus pointing to a preservation of the cardiac sympathetic control during pregnancy.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The primary role of the arterial baroreflex is the immediate and short-term adjustment of BP following perturbations around an existing mean pressure [ 32 ]. Baroreflex sensitivity (BRS) was reported to decrease from term to the postpartum period in normotensive pregnancy [ 32 35 ]. Valdes et al [ 36 ] demonstrated a progressive blunting of the heart rate response to tilt as pregnancy progressed, suggesting a decrease in BRS in late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women are prone to orthostatic hypotension, due to blunted reflex activation of the sympathetic nervous system and inadequate peripheral vasoconstriction (56,122,132). Moreover, in many species, pregnancy interferes with the normal ability to maintain arterial pressure during hemorrhage (26,36,99,152,186).…”
mentioning
confidence: 99%